THE IMPACT OF TEACHER COMPETENCE, SCHOOL ENVIRONMENT AND SPIRITUAL ACTIVITIES ON THE LEARNING ACHIEVEMENT OF STUDENTS OF SMP BATIK SURAKARTA - Nurul Hidayati; Bambang Mursito; Kartika Hendra Titisari (JURNAL ILMIAH EDUNOMIKA, 2020)
The problems presented relate to teacher competence, school environment and Spiritual Activities affect student achievement at SMP Batik Surakarta. This research method using research design is a survey research. This research was conducted at SMP Batik Surakarta in February 2020 - July 2020. The research reason was that learning achievement needs to be improved so that SMP Batik Surakarta students are able to obtain optimal learning achievement. The object of this study of Surakarta SMP Batik Surakarta, then of this research the population is totaling 303 students. The total population was 262 students from the total population, so in this study of C class is 33 students. The analysis tool used is regression research, t test, F test and R2 test. research result showed: there is influence of teacher competence, school environment and spiritual activities on the student achievement of Students in Surakarta Batik Junior High School partially and simultaneously Keywords: Teacher Competence, School Environment, Spiritual Activities and Student Achievement